Proper irrigation amount for eggplant cultivation in a solar greenhouse improved plant growth, fruit quality and yield by influencing the soil microbial community and rhizosphere environment - Ji, Tuo; Guo, Xinyong; Wu, Fengling; Wei, Min; Li, Jing; Ji, Ping; Wang, Ningxin; Yang, Fengjuan (Frontiers in Microbiology, 2022)
Water scarcity is a worldwide problem, and agricultural irrigation accounts for a large proportion of water use. Many studies have shown that the interaction of root microorganisms and soil can promote crop growth. Developing ways to reduce irrigation to maintain soil fertility and ensure crop yield by regulating the root microenvironment is an important research goal. Here, we developed a reasonable irrigation plan for eggplant cultivation in a solar greenhouse. The maximum theoretical amount of water demand during eggplant planting obtained from a previous study was used as the control (CK), and the irrigation in the treatments was reduced by 10%, 20% and 30% relative to this amount. The 10% irrigation reduction treatment (T1) significantly improved soil nutrients and increased soil catalase, urease and alkaline phosphatase activities (P<0.05). Further analysis of rhizosphere microorganisms revealed the highest richness and diversity of the microbial community under the T1 treatment, with Bacilli as the most abundant bacteria and Aspergillaceae as the most abundant fungi and lower relative abundances of Chloroflexi and Acidobacteria (P<0.05). Changes in microbial community structure under the influence of different irrigation treatments resulted in improvements in rhizosphere N cycling and nutrient catabolism. The plant–microbe interactions led to significant increases in eggplant plant height, root vigour, root surface area, leaf chlorophyll a, leaf net photosynthetic rate, water use efficiency, transpiration rate, and stomatal conductance under the T1 treatment compared to the CK treatment; soluble sugar, soluble protein and free amino acid contents in eggplant fruit increased by 10.8%, 12.3% and 6.7%, respectively; and yield increased by 3.9%. Our research proved that the 10% irrigation reduction treatment (T1) could improve microorganismal community richness and fruit yield, which would benefit irrigation efficiency and cost reduction in agriculture.